Red lines and compromises: mapping underlying complexities of Brexit preferences - Richards, L; Heath, A; Carl, N (John Wiley & Sons Ltd, 2018)
The political discourse is characterised by two opposing ideals of hard and soft Brexit. In this article, we present evidence of attitudinal types that map neatly onto these archetypal views. The hard Brexit view is defined by issues that eurosceptics prioritise, most prominently sovereignty. By contrast, europhiles prioritise cooperation with Europe in terms of scientific collaboration and market access. However, attitudinal types are not either/or in the minds of the British public, and many prioritise all or none of the issues. Further, the two opposing positions together account for 37 per cent of the public's view. That is, just over one‐third differentiate between the salient issues in ways congruent with political ideals. National identity plays a particular role in the sociodemographic profiles of these attitude types. Older people have a strong stance in any direction (sovereignty, cooperation, or both), but national identity is linked to differentiated positions (sovereignty only or cooperation only).